2019
DOI: 10.2478/s11686-019-00053-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China

Abstract: Introduction Haemaphysalis longicornis is an important ectoparasite of domestic and wild animals that can transmit many pathogens including viruses, fungi, bacteria and protozoa. Materials and methodsIn this study, we examined genetic variation and population genetics in three mitochondrial (mt) genes [cox1 (cytochrome c subunit 1), rrnL (large subunit ribosomal RNA) and nad5 (NADH dehydrogenase 5)] among four H. longicornis populations from China. ResultsThe sizes of the partial sequences of cox1, rrnL and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although this mt marker has been successfully applied to population genetic studies on acari (e.g. Li et al 2019), its use has not been previously reported in genetic studies of V. destructor populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although this mt marker has been successfully applied to population genetic studies on acari (e.g. Li et al 2019), its use has not been previously reported in genetic studies of V. destructor populations.…”
Section: Introductionmentioning
confidence: 99%
“…The tick Haemaphysalis flava Neumann is an important ectoparasite, which not only damages its hosts directly but also serves as a vector for various infectious pathogens in China (Cheng et al 2013, Lu et al 2013, Li et al 2017. Recent studies have also reported Haemaphysalis longicornis Neumann and Haemaphysalis hystricis Supino in China (Lu et al 2017, Wang et al 2018, Zhang et al 2018, Li et al 2019b, Yang et al 2019, Zheng et al 2019. Haemaphysalis bispinosa Neumann has been believed to occur in China, especially in the southern part.…”
mentioning
confidence: 99%